2022
DOI: 10.1051/0004-6361/202243064
|View full text |Cite
|
Sign up to set email alerts
|

A probabilistic method for detecting solar-like oscillations using meaningful prior information

Abstract: Context. Current and future space-based observatories such as the Transiting Exoplanet Survey Satellite (TESS) and PLATO are set to provide an enormous amount of new data on oscillating stars, and in particular stars that oscillate similar to the Sun. Solar-like oscillators constitute the majority of known oscillating stars and so automated analysis methods are becoming an ever increasing necessity to make as much use of these data as possible.Aims. Here we aim to construct an algorithm that can automatically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 70 publications
(57 reference statements)
2
6
0
Order By: Relevance
“…Starting with a smaller set of targets that were identified as the most likely to oscillate above the 30-min FFI Nyquist frequency (Schofield et al 2019), we have identified 400 candidate solar-like oscillators by eye. These were used to optimise a detection algorithm presented in Nielsen et al (2022; henceforth referred to as N22). We then passed the remaining stars observed during the aforementioned sectors to this tuned pipeline.…”
Section: Introductionmentioning
confidence: 99%
“…Starting with a smaller set of targets that were identified as the most likely to oscillate above the 30-min FFI Nyquist frequency (Schofield et al 2019), we have identified 400 candidate solar-like oscillators by eye. These were used to optimise a detection algorithm presented in Nielsen et al (2022; henceforth referred to as N22). We then passed the remaining stars observed during the aforementioned sectors to this tuned pipeline.…”
Section: Introductionmentioning
confidence: 99%
“…The novelty of FRA lies in its ability to assess whether or not a given star exhibits oscillations. To that matter, FRA performs a totally blind search for νmax$$ {\nu}_{\mathrm{max}} $$, independent from the normalΔν$$ \Delta \nu $$ measurement and using a different approach than that used by Nielsen et al (2022). We describe in the following the different steps we implemented.…”
Section: The Fra Pipeline To Detect Solar‐like Oscillations: Measurem...mentioning
confidence: 99%
“…TESS completed its 2‐year, all‐sky nominal survey in July 2020 and is dramatically increasing the number of red giants with detected oscillations, which is expected to be on the order of 105$$ 1{0}^5 $$ (Campante et al 2016; Hon et al 2021; Hon et al 2022; Mackereth et al 2021; Silva Aguirre et al 2020; Stello et al 2022). TESS enables in particular the measurement of the two global asteroseismic properties νmax$$ {\nu}_{\mathrm{max}} $$ and normalΔν$$ \Delta \nu $$, for red giants (Hon et al 2021, 2022; Mackereth et al 2021; Stello et al 2022) as well as for main‐sequence (MS) and subgiant (SG) stars (Nielsen et al 2022). The frequency of maximum oscillation power νmax$$ {\nu}_{\mathrm{max}} $$ is proportional to the surface gravity g$$ g $$ and effective temperature Teff$$ {T}_{\mathrm{eff}} $$ of the star such that (Brown et al 1991; Kjeldsen & Bedding 1995) νmaxgTeff.$$ {\nu}_{\mathrm{max}}\propto \frac{g}{\sqrt{T_{\mathrm{eff}}}}.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is because the power spectrum is calculated with a step size that must sample the frequency resolution, and this is inversely proportional to the total duration of the time series (including the gap). Because solar-like oscillators have finite mode lifetimes, it has become tempting to close large gaps by shifting time stamps and we are aware of several cases in which this has been done, both in published works (e.g., Hekker et al 2010;Nielsen et al 2022) and in papers in preparation. The justification is that mode lifetimes are much shorter than the gap, so shifting segments should not have much effect on the power spectrum.…”
Section: Introductionmentioning
confidence: 99%